Rationality, REMM, and Individual Value Creation - Wartiovaara, Markus (Journal of business ethics, 2011)
This article evaluates alternative models for explaining human behavior. In particular, it compares the resourceful, evaluative, maximizing model (REMM) with the economic (or money maximizing) model of human behavior. The theoretical framework is developed to enhance our understanding of “individual value creation” and to seek an economically rational explanation to: Why Warren Buffett is giving his money away to charity? The article develops a framework of biological, material, and immaterial sources of value. The article additionally extends the existing REMM and finds several economically rational reasons for him to give away his money including the present value of help and goodwill, gained control, and lowered transaction costs.